Da'wah Aqidah Imam Abul Hasan Ali Al-Asy'ari - Mustofa, Ahmat; Syafrin, Nirwan (Komunika: Journal of Communication Science and Islamic Dakwah, 2021)
This study discusses the da'wah of Aqidah Imam Abul Hasan Ali al-Asy'ari. The research objectives based on the formulation of the problem are as follows how to know the preaching of Imam Abul Hasan Ali al-Asy'ari's faith and to find out the history of Intellectual Development and the process of spreading da'wah Imam al-Asy'ari. This study uses the library research method or library research using a qualitative approach. The data sources used are primary and secondary data from books written by Imam Abul Hasan Ali al-Asy'ari, and supporting books related to research. Data collection techniques by collecting written archives in the form of books that have to do with research problems, which are then analyzed or analyzed. The results obtained that da'wah aqidah Imam Abul Hasan Ali al-Asy'ari is one of the schools built on the basis of the existing texts, so that this understanding is often referred to as ‘'Sunni' or 'Ahlussunnah.'' The theological formulation built by Imam al-Asy'ari does not only use rational arguments in the form of mantik or logic with the science of kalam, he also uses the textual argument in the form of the texts of the Qur'an and al-Sunnah as practiced by the hadith experts whom he follows his understanding in developing the faith of Ahlussunnah. From the object of this research, the author found that the preaching of the aqeedah of Imam Abul Hasan Ali al-Ash'ari is a form of renewal in the preaching of aqeedah which does have rational or logical arguments that cannot be separated from the Qur'an and as- Sunnah. Abstrak Penelitian ini membahas tentang da'wah Aqidah Imam Abul Hasan Ali al-Asy'ari.Tujuan penelitian ini untuk mengatahui da'wah aqidah Imam Abul Hasan Ali al-Asy'ari dan mengetahui sejarah Perkembangan Intelektual dan proses penyebaran da'wah aqidah Imam al-Asy'ari. Penelitian ini menggunakan metode library research atau penelitian kepustakaan dengan menggunakan pendekatan kualitatif. Adapun sumber data yang digunakan adalah data-data primer dan sekunder dari buku-buku yang ditulis oleh Imam Abul Hasan Ali al-Asy'ari, serta buku pendukung yang berkaitan dengan penelitian. Teknik pengumpulan data dengan mengumpulkan arsip tertulis berupa buku-buku yang ada hubungannya dengan masalah penelitian, yang kemudian data tersebut di telaah atau dianalisa. Hasil yang diperoleh bahwa da'wah aqidah Imam Abul Hasan Ali al-Asy'ari merupakan salah satu aliran yang di bangun berdasarkan landasan nash-nash yang ada, sehingga paham ini sering disebut dengan ‘'sunni atau ahlussunnah.'' Rumusan teologi yang dibangun oleh Imam al-Asy'ari tidak hanya menggunakan argument rasional berupa mantik atau logika dengan ilmu kalam, ia juga menggunakan argument tekstual berupa teks-teks al-Qur'an dan al-Sunnah seperti yang dilakukan oleh ahli hadits yang ia ikuti pemahamannya dalam mengembangkan aqidah ahlussunnah. Dari objek penelitian ini, penulis menemukan bahwasannya da'wah aqidah Imam Abul Hasan Ali al-Asy'ari adalah salah satu bentuk pembaharuan dalam da'wah aqidah yang memang memiliki argumentasi rasional atau logika yang tidak terlepas dari al-Qur'an dan as-Sunnah.